Baseline White Matter Is Associated With Physical Fitness Change in Preclinical Alzheimer’s Disease - Venkatraman, Vijay K.; Steward, Christopher E.; Cox, Kay L.; Ellis, Kathryn A.; Phal, Pramit M.; Sharman, Matthew J.; Villemagne, Victor L.; Lai, Michelle M. Y.; Cyarto, Elizabeth V.; Ames, David; Szoeke, Cassandra; Rowe, Christopher C.; et al. (Frontiers in Aging Neuroscience, 2020)
White matter microstructure is a sensitive marker to distinguish individuals at risk of Alzheimer’s disease. The association of objective physical fitness measures and white matter microstructure has not been explored and mixed results reported with physical activity. Longitudinal studies of white matter with physical activity and physical fitness measures has had limited investigation. This study explored the relationship between objective physical fitness measures over 24-months with ‘normal appearing’ white matter microstructure. Data acquired on magnetic resonance imaging was used to measure ‘normal appearing’ white matter microstructure at baseline and 24-months. Clinical variables such as cognitive, blood-based measures were collected longitudinally. Also, as part of the randomized controlled trial of physical intervention, extensive measures of physical activity and fitness were obtained over the 24-month period. Bilateral corticospinal tracts and corpus callosum showed significant association between physical fitness performance over 24-months and baseline white matter microstructural measures. There was no significant longitudinal effect of intervention or physical fitness performance over 24-months. Baseline white matter microstructural measures significantly associated with physical fitness performance over 24-months in this cohort of participants with vascular risk factors and at risk of Alzheimer’s disease with distinctive pattern for each physical fitness test.